Identification of Some α-Glucosidase Inhibitors Using QSAR Modeling Based Drug Repurposing Approach - Sonu , Dr; Kori, Mohan Lal (Journal of Drug Delivery and Therapeutics, 2025)
Post-prandial hyperglycemia still remains a problem in the management of type II diabetes mellitus. Of all available anti-diabetic drugs, α-glucosidase inhibitors seem to be one of the most effective in reducing post-prandial hyperglycemia. In present study, QSAR modeling based drug repurposing approach has been implemented to identify some repurposed α-glucosidase inhibitors with established safety profile. For this QSAR modeling based analysis, initially a series of N’-Benzylidenebenzoylhydrazide having two different types of substitutions on Benzylidene and Benzoyl part as well as proper variation in the biological activity was selected thereafter models were developed using various conventional QSAR approaches including Free Wilson, Hansch, and Mixed modeling by utilizing PaDEL descriptor calculator and DTC lab software. Hansch type 2D QSAR model, which was derived using some PaDEL descriptor, showed acceptable internal as well as external consistencies. Some repurposed α-glucosidase inhibitors were successfully identified. These identified approved drugs may be further explored as new anti-diabetics for type II diabetes patient especially for the management of post-prandial hyperglycemia which is a major issue in these patients. Keywords: QSAR, Hyperglycemia, Substitutions, Diabetes mellitus, PaDEL descriptor